Prevention-of-Mother-To-Child-Transmission of HIV Services in Sub-Saharan Africa: A Qualitative Analysis of Healthcare Providers and Clients Challenges in Ghana - Amos Kankponang Laar, PhD; Belynda Amankwa, MPH; Charlotte Asiedu, MPH (Global Health and Education Projects, Inc., 2015)
Background: Developed by the World Health Organization (WHO) and partners, the correct adaptation and implementation of the global guidelines on prevention of mother-to-child transmission (PMTCT) of HIV is critical. This study explored the challenges that health workers face implementing WHO's PMTCT guidelines, and the experiences of HIV-positive clients receiving these services. Methods: We interacted with 14 health professionals, and 16 PMTCT clients through in-depth interviews. Four of seven PMTCT sites within the Accra Metropolis were purposively included. Interviews were tape-recorded, transcribed, analyzed, and then sorted into themes. Results: Health workers had challenges translating PMTCT guidelines into useful messages for their clients. Their counseling was often prescriptive. Counselors identified inadequate in-service training as a key reason for their outdated and inconsistent messages. HIV-positive clients exhibited general knowledge about the importance of doing exclusive breast-feeding for the first six months of life. Clients had confidence in antiretroviral for PMTCT. However, deeply rooted socio-cultural practices and the attitudes of counselors remain challenges to clients. Conclusions and Global Health Implications: Counselors require refresher training which addresses, among other things, long-held socio-cultural practices. Publicizing these challenges will prod policy makers and program implementers to develop strategies that address the challenges both locally and globally. Key Words : HIV • Service providers • Clients • PMTCT • Challenges Copyright © 2014 Laar et al. This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.